Menjelajahi Dinamika Pengambilan Keputusan Keuangan UKM: Pendekatan Kualitatif pada Aspek Kewirausahaan di Desa Glondonggede Tambakboyo - A’yun, Inarotul; Rustyawati, Dian; Yuliartin, Fenti (Journal of Islamic Finance and Syariah Banking, 2024)
This study analyzes the dynamics of financial decision-making in small and medium-sized enterprises (SMEs) using a qualitative approach that focuses on the entrepreneurial aspect in Glondonggede Village, Tambakboyo. SMEs play a vital role in the local economy, but effective and adaptive financial management remains a challenge. The entrepreneurial aspect, encompassing innovative thinking, flexibility, and a willingness to take risks, is increasingly recognized as a crucial factor in the SME financial decision-making process. This research employs a qualitative approach through in-depth interviews and content analysis to explore how entrepreneurial characteristics influence financial decision-making at the local level. The research findings reveal that owners and managers of SMEs in Glondonggede Village have a strong long-term vision related to their business goals. The entrepreneurial aspect provides them with the ability to adapt quickly to changes in the business environment and develop innovative solutions to address financial constraints. SME owners and managers also demonstrate a readiness to take measured risks to achieve long-term business objectives.